Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Nasabah: Peran Mediasi Kepercayaan pada PT Jasa Raharja Putera Cabang Ambon - Endro Kuswoyo; Mashur Razak; Muh. Ashary Anshar (Center of Economic Students Journal, 2026)
This study examines the effects of product quality and service quality on customer satisfaction through trust at PT Jasa Raharja Putera Ambon Branch. A quantitative survey design was applied. The population comprised 2,000 customers, while the sample consisted of 100 suretyship customers selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using partial least squares structural equation modeling in SmartPLS 4. Product quality positively affected trust (β = 0.389; p < 0.001) and customer satisfaction (β = 0.223; p = 0.014). Service quality positively affected trust (β = 0.545; p < 0.001) and customer satisfaction (β = 0.252; p = 0.011). Trust also positively affected customer satisfaction (β = 0.362; p = 0.003). The indirect effect of product quality through trust was 0.141 (p = 0.007), whereas the indirect effect of service quality was 0.198 (p = 0.008). Both patterns indicate complementary partial mediation. The model explained 56.9% of the variance in trust and 48.5% of the variance in customer satisfaction, with an SRMR value of 0.065. Descriptively, service quality obtained the lowest mean score but exerted the strongest effect on trust. The findings demonstrate that improving insurance customer satisfaction requires more than better product features; it also requires consistent service delivery, transparent information, responsiveness, and reliable fulfillment of corporate promises that strengthen customer trust.